Loneliness, coping practices and masculinities in later life: Findings from a study of older men living alone in England. (26th January 2022) - Willis, Paul; Vickery, Alex
Abstract: While much attention has been given to loneliness as a public health and societal problem less consideration has been given to men's experiences, particularly in later life, and there is a limited evidence based on what works with supporting older men to counteract the impact of loneliness on their mental and social wellbeing. In this paper, we focus on the experiences of older men living alone in the community. Between 2017–2018 72 men residing in England (65–95 years) took part in the study and shared their accounts of experiencing and addressing loneliness on an everyday basis. We generated qualitative data through semi‐structured interviews. Interview data were analysed thematically using the framework analysis approach. We present and discuss findings on the difficulties older men experience in responding to and discussing loneliness and the range of coping practices men applied within their home environments. Three core themes are presented: 1. Maintaining silence around loneliness and distress; 2. Getting on with it versus feeling stuck in loneliness and, 3. Temporary remedies and distractions from loneliness from within the home. Across men's accounts, 'the home' is constructed as a space of biographical connections with others as well as a restrictive environment of separation from others. In relation to help‐seeking and efforts to break silence surrounding loneliness, the findings speak to the ways in which masculinities and social expectations attached to male roles complicate older men's varying attempts at help‐seeking and underpin some of their everyday methods of coping with loneliness. The findings reiterate the importance of targeted individual support for older men, particularly for those feeling frozen in loneliness. Facilitators of group‐based support for older men need to recognise the different and potentially conflicting positions older male service users may adopt in relation to help‐seeking that are configured around masculine ideals but in diverging ways.